Chemical activation of hollow carbon nanospheres induced self-assembly of metallic 1T phase MoS2 ultrathin nanosheets for electrochemical lithium storage. (1st September 2020) - Liu, Yanguo; Chen, Jiayuan; Xu, Chang; Yu, Tingli; Li, Zhipeng; Wei, Zhiqiang; Qian, Lizhi; Wan, Yanfen; Yang, Peng; Wang, Zhiyuan; Luo, Shaohua; Sun, Hongyu
Abstract: Ultrathin nanosheets made by transition metal dichalcogenide show the potential as high-capacity anode materials for lithium ion batteries (LIBs). However, the tendency of restacking individual nanosheet due to strong van der Waals force, a dramatic volume variation upon continuous cycling, as well as poor intrinsic conductivity greatly restrict their practical applications. In this work, high content metallic phase molybdenum disulfide (1T/2H–MoS2 ) ultrathin nanosheets with higher intrinsic conductivity and extended interlayer distance are vertically assembled on the outer surface of chemically activated hollow carbon nanospheres (CAHCSs) through a facile solvothermal method. Phase structure, chemical composition, and microstructure studies show that the obtained composites (CAHCSs@1T/2H–MoS2 ) have optimized structural and compositional advantages to efficiently store lithium ions. When evaluated as anodes for LIBs, the CAHCSs@1T/2H–MoS2 electrode show excellent fast and stable lithium storage properties. In specific, the CAHCSs@1T/2H–MoS2 electrode delivers a large reversible capacity of 831 mAh g −1  at 1 A g −1 after 200 cycles. At a higher current density of 2 A g −1, the CAHCSs@1T/2H–MoS2 electrode has a reversible capacity of 863 mAh g −1 . The proposed electrode design strategy provides an alternative route to promote the ion storage in transition-metal-dichalcogenides-based materials. Graphical abstract: The vertically assembled metallic phase molybdenum disulfide ultrathin nanosheets on the outer surface of chemically activated hollow carbon nanospheres exhibit excellent lithium storage properties. Image 1 Highlights: MoS2 ultrathin nanosheets are self-assembled on hollow carbon nanospheres. The MoS2 nanosheets contain ∼77.8% metallic 1 T phase. The optimized sample exhibits enhanced lithium storage properties.